2019
DOI: 10.1111/imj.14159
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is associated with reduced prospect of discharge home after in‐hospital cardiac arrest

Abstract: Background Frailty is common among acute hospital patients and might adversely affect recovery from inpatient cardiac arrest. Aim To assess the relationship between hospital admission characteristics, including frailty, and discharge outcome after in‐hospital cardiac arrest. Methods Prospectively collected data were retrospectively analysed for all separations from a tertiary hospital during 2008–2017 that involved rapid response team attendance for cardiac arrest. Hospital Frailty Risk Score (HFRS) and Charls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Worldwide, Smith et al's Australian retrospective 10-year analysis first demonstrated a decreased likelihood of discharge from hospital for the frailest patients, but could not demonstrate an independent association with worsened survival. 16 This publication used the Hospital Frailty Risk Score (HFRS) to calculate patient frailty. The retrospective reviews of Ibitoye et al 14 and Wharton et al 13 are two other publications assessing the relationship between frailty and CPR outcome that have been published since we began collecting our data.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, Smith et al's Australian retrospective 10-year analysis first demonstrated a decreased likelihood of discharge from hospital for the frailest patients, but could not demonstrate an independent association with worsened survival. 16 This publication used the Hospital Frailty Risk Score (HFRS) to calculate patient frailty. The retrospective reviews of Ibitoye et al 14 and Wharton et al 13 are two other publications assessing the relationship between frailty and CPR outcome that have been published since we began collecting our data.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age and comorbidity burden are related to frailty, which describes a state of physiological decline and vulnerability 87. Future research should aim to investigate the association between frailty and outcomes after in-hospital cardiac arrest to help clinicians make a more accurate prognosis for patients admitted to hospital 88…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that age does not always correlate with outcome and is not in itself an adequate prognostic factor, as two elderly persons of the same age can have very different medical conditions [29]. High frailty and a low performance status have been connected with higher ECPSFNO and mortality in previous studies [30][31][32][33]. The increased mortality related to age in this study is indeed partially explained by the pre-admission functional status of the elderly patients; thus, this in combination with age seems to better predict both mortality and neurological outcome.…”
Section: Discussionmentioning
confidence: 99%